Jet-induced star formation in gas-rich galaxies - Gaibler, Volker (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. Feedback from active galactic nuclei (AGN) has become a major component in simulations of galaxy evolution, in particular for massive galaxies. AGN j